Promoting Pulmonary Arterial Growth via Right Ventricle-to-Pulmonary Artery Connection in Children With Pulmonary Atresia, Ventricular Septal Defect, and Hypoplastic Pulmonary Arteries. (September 2017) - Rabinowitz, Edon J.; Epstein, Shilpi; Kohn, Nina; Meyer, David B.
Background: Complete repair of pulmonary atresia (PA) ventricular septal defect (VSD) with hypoplastic or absent native pulmonary arteries, often with major aortopulmonary collateral arteries (MAPCAs), involves construction of an adequate sized pulmonary arterial tree. We report our results with a previously described staged strategy using initial right ventricle (RV)-to-reconstructed pulmonary arterial tree (RV-PA) connection to promote pulmonary arterial growth and facilitate later ventricular septation. Methods: We retrospectively reviewed data for all patients (N = 10) with initial echocardiographic diagnosis of PA-VSD and hypoplastic pulmonary arteries operated in our center from October 2008 to August 2016. Pulmonary arterial vessel size measured on preoperative and postoperative angiography was used to calculate Nakata index. Results: Seven patients had PA-VSD, three had virtual PA-VSD, and seven had MAPCAs. All underwent creation of RV-PA connection at a median age of 7.5 days and weight 3.6 kg. Eight patients had RV-PA conduits, two had a transannular patches, and seven had major pulmonary artery reconstruction simultaneously. There were no deaths or serious morbidity; one conduit required revision prior to complete repair. Complete repair with ventricular septation and RV pressure less than half systemic was achieved in all patients at a median age of 239 days. Nakata index in neonatal period was 54 mm 2 /m 2 (range 15-144 mm 2 /m 2 ) and at time of septation 184 mm 2 /m 2 (range 56-510 mm 2 /m 2 ; P = .004). Growth rates of right and left branch pulmonary arteries were similar. The 10 patients underwent 28 catheterizations with 13 interventions in 8 patients prior to full repair. Conclusion: Early palliative RV-PA connection promotes pulmonary arterial growth and facilitates eventual full repair with VSD closure with low RV pressure and operative risk.